2019
DOI: 10.1002/jts.22390
|View full text |Cite
|
Sign up to set email alerts
|

Supporting a Spouse With Military Posttraumatic Stress: Daily Associations With Partners’ Affect

Abstract: Service members and veterans (SM/Vs) with posttraumatic stress disorder (PTSD) can receive significant benefits from social support by a spouse or romantic partner. However, little is known about how providing support impacts partners. This study sought to identify (a) how provision of support is associated with partners' daily negative and positive affect and (b) how SM/Vs' PTSD symptom severity might moderate such associations. In a 14-day daily-diary study that assessed 64 couples in which one member was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Moreover, results suggest that providing health-related social support to the romantic partner is also related with providers’ higher emotional and relational well-being, supporting and extending previous diary work beyond the context of stress (e.g., Gleason et al, 2008 ; Carter et al, 2019 ) or illness (e.g., Kleiboer et al, 2006 ; Belcher et al, 2011 ; Kroemeke et al, 2019 ). One explanation may again be that supporting the partner for example by engaging in activity together may foster feelings of companionship and cohesion.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, results suggest that providing health-related social support to the romantic partner is also related with providers’ higher emotional and relational well-being, supporting and extending previous diary work beyond the context of stress (e.g., Gleason et al, 2008 ; Carter et al, 2019 ) or illness (e.g., Kleiboer et al, 2006 ; Belcher et al, 2011 ; Kroemeke et al, 2019 ). One explanation may again be that supporting the partner for example by engaging in activity together may foster feelings of companionship and cohesion.…”
Section: Discussionsupporting
confidence: 81%
“… Gleason et al (2003) for example found that providing support to the partner one day was associated with less negative mood that same day. Similarly, positive effects on own same-day mood or well-being indicators were found in patients with multiple sclerosis and their partners ( Kleiboer et al, 2006 ), in cancer patients and caregivers following stem cell transplantation ( Kroemeke et al, 2019 ), same-gender undergraduate friend dyads ( Morelli et al, 2015 ), and spouses of individuals with military posttraumatic stress ( Carter et al, 2019 ). Positive effects of daily reports of providing support to the romantic partner on providers’ relationship outcomes were also confirmed, e.g., higher daily intimacy in couples coping with breast cancer ( Belcher et al, 2011 ), more feelings of closeness and decreased negative affect in examinees preparing for the bar exam ( Gleason et al, 2008 ), or higher daily relationship satisfaction, but only in the context of positive event disclosure ( Gosnell and Gable, 2015 ).…”
Section: Introductionmentioning
confidence: 98%
“…Two diary studies conducted with U.S. service members emphasize how daily support from a partner can be helpful for both individuals and relationships. In terms of personal benefits, Carter et al (2019) found that on days when partners offered support to a service member or veteran with PTSD symptoms, partners reported a same-day increase in their own positive affect and a same-day decrease in their own negative affect. In other words, offering support can be personally rewarding for helpers.…”
Section: Narrative Synthesismentioning
confidence: 99%